Gender differences in the associations between tobacco smoke exposure and depressive symptoms among U.S. adults: NHANES 2007–2018. (February 2022) - Fan, Zhixin; Gong, Xiayu; Xu, Hanfang; Wang, Hanzhang; Zeng, Ningxi; Li, Ling; Yan, Can; Wu, Lili; Chen, Yuan
Abstract: Background: Findings concerning gender differences in the associations between tobacco smoke exposure (TSE) and depression are inconsistent. This study aimed to investigate the gender-specific associations between active and passive TSE with depressive symptoms in a large, nationally representative sample of U.S. adults. Methods: Data were from 27, 175 adults aged ≥20 years in the 2007–2018 National Health and Nutrition Examination Survey (NHANES). Depressive symptoms were assessed using the Patient Health Questionnaire-9 (PHQ-9). Multivariable logistic regression was used to adjust for possible confounders. Whether the TSE-depression relationships may differ by age, race/ethnicity, socioeconomic status, body mass index (BMI), and self-reported health status was examined. Results: After adjustment for lifestyle- and health-related variables, no significant associations between active (OR, 1.16 [95% CI, 0.87–1.55]) and passive TSE (OR, 0.84 [95% CI, 0.59–1.19]) and depressive symptoms were found among men. Among women, active TSE was associated with depressive symptoms (OR, 1.90 [95% CI, 1.51–2.39]), while the association for passive TSE was nonsignificant (OR, 1.11 [95% CI, 0.91–1.34]) after adjusting for lifestyle- and health-related variables. Interaction and subgroup analyses showed that self-reported health status could modify the relationship between passive TSE and depressive symptoms among women. Furthermore, a dose-response relationship between serum cotinine and depressive symptoms was found in women, but not in men. Conclusions: This study suggests a stronger TSE-depression association in women than in men. Understanding these gender-specific patterns and identifying the potential moderators of such relationships will enable better targeting of public health interventions. Highlights: Active smoking was associated with depression among women. Passive smoke exposure was not significantly associated with depression in either gender. A dose-response relationship between serum cotinine and depression was found in women, but not in men.